EFFECTIVENESS OF GUIDED INQUIRY BASED WORKSHEET TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS ON THE MATERIAL OF VIRUS REPLICATION - Permatasari, Anggi; Tri Asri, Mahanani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of guided inquiry based worksheet on virus replication material to improve critical thinking skills of grade X high school students. The study used the method Research and Development (R&D) with a 4D development model (Define, Design, Develop, And Disseminate). A limited trial was conducted on 30 grade X high school students. The research instrument used was a critical thinking skills test based on Facione (2015) indicators, namely interpretation, analysis, inference, evaluation, explanation, and self-regulation. Data were analyzed using percentages and N-gain. The results showed that worksheet effectively improved critical thinking skills with an average pre-test score of 80.83 and a post-test score of 96.95, as well as an average N-gain of 0.84, categorized as high. Thus, the guided inquiry based student worksheet on virus replication was declared effective in improving students' critical thinking skills.